(3eMGSHI GdTQcGJ (B:s (3CTNGU hCehGd (B/s - (3TMGJI, CMeO Hjhfjs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI ddfTQ hGdJhRjY(B, s, 1987)
(3aj GdeTGcd GdeMGSHjI TQcGJ GdCTNGU ,Jchjf TQcGJ GdJVGef hGdJhUjI GdHSjWI ,bjGS hJhRjY GdCQHGM hGdNSGFQ ,JYOjd GdTQcI ,GdJUajI hGdEfOeGL ,TQcGJ GdeMGUI ,aj GdeTGcd GdeMGSHjI dTQcI GdCehGd ,aj TQcGJ GdeSGgeI ,GdSfOGJ ,aj EYOGO GdbhGFe GdeGdjI GdeLeYI ddTQcGJ GdbGHVI hGdTQcGJ GdJGHYI dgG ,EYOGO GdbhGFe GdeGdjI GdeLeYI ,EYOGO GdbhGFe GdeLeYI HYO JGQjN GdEbJfGA (B.s
Keywords: (3GdTQcGJ(B- (3eMGSHIs; (3GdeDSSGJ GdGbJUGOjIs